1982
DOI: 10.1021/ja00373a039
|View full text |Cite
|
Sign up to set email alerts
|

Benzannulated annulenes. 9. Toward the understanding of benzannulated annulenes: a simple correlation of the diatropicity of several benzannulated dihydropyrenes in terms of bond order deviations with predictions for other benzannulenes

Abstract: Zwischen der Abschirmung der chemischen Verschiebung von inneren Protonen der benzanellierten Dihydropyrene (l )‐(V) und der mittleren Abweichung von der π‐Bindimgsordnung für den Makrocyclils von [14]Annulen besteht ein linearer Zusammenhang; vergleichbare Ergebnisse werden für die Dehydro[l4]annulene (VD‐(VIII) erhalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 3 publications
2
23
0
Order By: Relevance
“…Effect of Conjugation. A simple correlation of the diatropicity of benzannelated dihydropyrenes in terms of bond order deviation has been employed successfully to predict the chemical shift of the methyl protons in derivatives of 1 . Similar calculations on 6 and 11 in our work afforded the results summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Effect of Conjugation. A simple correlation of the diatropicity of benzannelated dihydropyrenes in terms of bond order deviation has been employed successfully to predict the chemical shift of the methyl protons in derivatives of 1 . Similar calculations on 6 and 11 in our work afforded the results summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…The explanation is given in the 1990 paper, 63 and principally rests on looking at the relative resonances of the annulene vs. the annulated moiety. In a series of papers, [64][65][66][67][68] Mitchell showed that when a benzene is annulated (3 and 4), the chemical shift of the central H and Me is shifted downfield by 4.14 and 2.65 ppm, respectively, for 3, and by 2.4 ppm for 4. For 5 and 6, it was found that the chemical shift of the central Me groups is 0.02 and À3.58 ppm, respectively.…”
Section: Nmrmentioning
confidence: 99%
“…Numerous recent studies have shown that Boekelheide's trans -15,16-dimethyl-dihydropyrene (DMDHP) 1 , a 14π-diatropic annulene, with its highly shielded internal methyl groups is a sensitive probe for monitoring the ring current effects and aromaticity in annulenes (Figure ). …”
Section: Introductionmentioning
confidence: 99%
“…The syntheses of [a]ring- and [e]ring-benzannelated dihydropyrenes ,, and their PAH-fused analogues (e.g., naphtho-, pyreno-, phenanthro-, biphenyleno-, and acenaphthyleno-DMDHP) 4,8-10 have been accomplished. Several heteroaromatic-fused counterparts (e.g., furan and thiophene) were also synthesized, and their ring current effects were examined. , …”
Section: Introductionmentioning
confidence: 99%